2020
DOI: 10.18632/aging.102913
|View full text |Cite
|
Sign up to set email alerts
|

APEX1 is a novel diagnostic and prognostic biomarker for hepatocellular carcinoma

Abstract: In this study, we analyzed the expression and clinical significance of apyrimidinic endodeoxyribonuclease 1 (APEX1) in hepatocellular carcinoma (HCC). The APEX1 mRNA and protein levels were significantly higher in HCC than adjacent normal liver tissues in multiple datasets from the Oncomine, GEO and TCGA databases. APEX1 levels were significantly higher in early-stage HCC patients with low alpha-fetoprotein expression. The positive predictive value (PPV) for APEX1 was significantly higher than the PPV for alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…The data revealed that patients with lymph node invasion or distant metastasis had increased P-Rex1 expression in tumors (Figure 2B and C ). AFP is the gold standard biomarker for HCC diagnosis, and some studies have also revealed that AFP can predict prognosis during HCC treatment[ 29 , 30 ]. Thus, we also evaluated the correlation between P-Rex1 and AFP.…”
Section: Resultsmentioning
confidence: 99%
“…The data revealed that patients with lymph node invasion or distant metastasis had increased P-Rex1 expression in tumors (Figure 2B and C ). AFP is the gold standard biomarker for HCC diagnosis, and some studies have also revealed that AFP can predict prognosis during HCC treatment[ 29 , 30 ]. Thus, we also evaluated the correlation between P-Rex1 and AFP.…”
Section: Resultsmentioning
confidence: 99%
“…Also, APEX1 was reported to be associated with some cancer types, including the cancers of colon, stomach, liver, kidney, and breast, as well as osteosarcoma[ 4 - 8 , 33 ]. Recent studies showed that APEX1 is an efficient biomarker for the diagnosis and prognosis of liver cancer[ 6 , 8 , 34 ]. However, the role of APEX2 in cancer is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Apyrimidinic endodeoxyribonuclease contains two members, namely, APEX1 and APEX2[ 3 ]. Having been widely reported in the pathogenesis of many cancers, especially in liver cancer[ 4 - 8 ], APEX1 was recently identified as a new diagnostic and prognostic biomarker for liver hepatocellular carcinoma (LIHC)[ 6 , 8 ]. However, the role of APEX2 in LIHC remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…As described previously ( 13 ), published data in the Oncomine™ database (oncomine.org/resource/main.html) was investigated to analyze the CLEC4M mRNA levels in unpaired non-tumor liver tissue samples and HCC tissue samples to determine the clinical importance of CLEC4M in HCC. The threshold settings were set to P<0.0001, fold change ≥2 and Gene rank=top 10%.…”
Section: Methodsmentioning
confidence: 99%